Museum specimens provide phylogenomic data to resolve relationships of sack‐bearer moths (Lepidoptera, Mimallonoidea, Mimallonidae). (31st May 2018) - St Laurent, Ryan A.; Hamilton, Chris A.; Kawahara, Akito Y.
Abstract: Mimallonidae, the sack‐bearer moths, are a family of predominantly Neotropical moths containing nearly 300 described species. Mimallonidae feed on over 40 host plant families and are found in a variety of environments, but phylogenetic relationships of species within the family have never been investigated. We sequenced 515 loci using anchored hybrid enrichment target capture on ethanol‐preserved and dried museum specimens, with dates of collection ranging from 1985 to 2017. We sampled 47 species, representing 32 of the 36 described mimallonid genera. By incorporating 19 dry museum specimens, and recovering an average of over 400 loci for each, we illustrate the utility of natural history collections in anchored hybrid enrichment‐based phylogenomics. Maximum likelihood and multi‐species coalescent analyses provide robust support for the recognition of six higher‐level groups within Mimallonidae, which we designate as subfamilies: Zaphantinae St Laurent & Kawaharasubfam.n., Aurorianinae St Laurent & Kawaharasubfam.n., Mimalloninae Burmeister, Lacosominae Dyar, Druenticinae St Laurent & Kawaharasubfam.n. and Cicinninae Schausstat.n. Our phylogenetic results also robustly support eight new tribes: Lacosominae: Trogopterini St Laurent & Kawaharatribe n., Lacosomini Dyarstat.n., Alheitini St Laurent & Kawaharatribe n. ; Druenticinae: Luramini St Laurent & Kawaharatribe n., Druenticini St Laurent & Kawaharatribe n. ; Cicinninae: Bedosiini St Laurent & Kawaharatribe n., Psychocampini St Laurent & Kawaharatribe n., Cicinnini Schausstat.n. Three new genera are also described based on our phylogenetic results: Herbinalla St Laurent & Kawahara, gen.n., Ulaluma St Laurent & Kawahara, gen.n., Bedosiallo St Laurent & Kawahara, gen.n. Naniteta Franclemont, syn.n. is a synonym of Lacosoma Grote. Six genera are paraphyletic, and in total 19 new combinations are proposed: Macessoga laxa comb.n., Lacosoma elassa comb.n., Thaelia anysia comb.n., Thaelia subrubiginosa comb.n., Herbinalla caudina comb.n., Druentica brosica comb.n., Ulaluma valva comb.n., Cicinnus eminens comb.n., Roelmana pluridiscata comb.n., Roelmana laguerrei comb.n., Psychocampa joanna comb.n., Psychocampa unalca comb.n., Psychocampa hamata comb.n., Psychocampa marona comb.n., Bedosiallo eugenia comb.n., Bedosiallo forbesi comb.n., Bedosiallo moengus comb.n., Bedosiallo styx comb.n. and Bedosiallo sylvia comb.n. This study is the first to implement the LEP1 probe set on a comprehensive taxonomic dataset that includes many museum specimens, and our results demonstrate that museum specimens can be used in anchored hybrid enrichment studies. Importantly, these data produce a robust phylogeny that will serve as a foundation for future studies on mimallonid evolution, such as host plant relationships and biogeography. This published work has been registered in ZooBank:http://zoobank.org/urn:lsid:zoobank.org:pub:60890688‐2E77‐4B98‐B247‐B7A5F7E4DFD9 . Abstract : We conducted the first phylogenetic analysis of Mimallonidae, sequencing 515 loci using anchored hybrid enrichment target capture from 47 species, representing 32 of the 36 described mimallonid genera. Maximum likelihood and multi‐species coalescent analyses provide robust support for the recognition of six higher‐level groups within Mimallonidae, which we designate as subfamilies. Three new genera are described: Herbinalla gen.n., Ulaluma gen.n., Bedosiallo gen.n. ; one new genus synonym and 19 new combinations are proposed.